The Active Compensation Technique for Large Reflector Antennas Based on Quadratic Curve Fitting - Zheng, Tian-Xiang; Xiang, Bin-Bin; Cui, Han-Wei; Wang, Wei; Lian, Pei-Yuan; Lin, Shang-Ming; Zhang, Yang; Zhou, Jian-Ping; Li, Kai (Research in astronomy and astrophysics, 2024)
Active reflectors are often used to compensate the surface distortion caused by environmental factors that degrade the electromagnetic performance of large high-frequency reflector antennas. This is crucial for maintaining high gain operation in antennas. A distortion compensation method for the active reflector of a large dual-reflector antenna is proposed. A relationship is established between the surface deformation and the optical path difference for the primary reflector by geometric optics. Subsequently, employing finite element analysis, a polynomial fitting approach is used to describe the impact of adjusting points on the reflector surface based on the coordinates of each node. By standardizing the positions of various panels on the reflector, the fitting ns can be applied to the reflector panels of similar shapes. Then, based on the distribution characteristics of the primary reflector panels, the adjustment equation for the actuators is derived by the influence matrix method. It can be used to determine the adjustment amount of actuators to reduce the rms of the optical path difference. And, the least squares method is employed to resolve the matrix equation. The example of a 110 m aperture dual-reflector antenna is carried out by finite element analysis and the proposed method. The results show that the optical path difference is reduced significantly at various elevation cases, which indicates that the proposed method is effective.